Swedish King Charles XII and the Development of Russia as a Great Empire - P. A. Krotov (Научный диалог, 2019)
The results of the personality analysis of the Swedish king Charles XII are presented. Sweden was led by a bright charismatic personality with his own concept of government and his military leadership style - King Charles XII. The questions of the influence of personality and the concept of the reign of Charles XII on the course and results of his state and military activities are examined. The author of the article claims that it was Charles XII’s personal qualities that “helped” Peter I to fully unleash the potential inherent in him by nature, upbringing and education. A connection is made between these historical figures: the more stubbornly and longer the king embodied his life concept into reality, put his paradigm of ideas into action, the more he made it possible for Tsar Peter I to express his genius as a statesman, commander and naval commander. It is proved that the fundamental personality traits of the Swedish king, his stubborn longstanding, accompanied by the highest degree of resource mobilization, the war with Peter I contributed to the formation of the corresponding counterweight - the Russian Empire. In the author’s opinion, if history had not given Peter I such a charismatic adversary, he would have every chance to make it into history as Tsar Peter I, but not as Emperor Peter the Great. It is emphasized that the stubbornness, uncompromisingness of Charles XII, paradoxically, created Great Russia.